On the nature of the Mott transition in multiorbital systems - Facio, Jorge Ismael (2017)
We analyze the nature of a Mott metal-insulator transition in multiorbital systems using dynamical mean-field theory. The auxiliary multiorbital quantum impurity problem is solved using continuous-time quantum Monte Carlo and the rotationally invariant slave-boson (RISB) mean-field approximation. We focus our analysis on the Kanamori Hamiltonian and find that there are two markedly different regimes determined by the nature of the lowest-energy excitations of the atomic Hamiltonian. The RISB results at T → 0 suggest the following rule of thumb for the order of the transition at zero temperature: a second-order transition is to be expected if the lowest-lying excitations of the atomic Hamiltonian are charge excitations, while the transition tends to be first order if the lowest-lying excitations are in the same charge sector as the atomic ground state. At finite temperatures, the transition is first order and its strength, as measured, e.g., by the jump in the quasiparticle weight at the transition, is stronger in the parameter regime where the RISB method predicts a first-order transition at zero temperature. Interestingly, these results seem to apply to a wide variety of models and parameter regimes.